Efficacy of three biopesticides against cucurbit fruit fly, Bactrocera cucurbitae Coquillett (Diptera: Tephritidae) and yield of bitter gourd: Efficacy of three biopesticides against cucurbit fruit fly (Journal of the Bangladesh Agricultural University, 2019)
The cucurbit fruit fly, Bactrocera cucurbitae ((Diptera : Tephritidae)) is a significant threat to different cucurbits. The efficacies of three biopesticides viz. Spinosad, Abamectin and Lecanicillium muscarium either by an individual or their combined application were evaluated against the insect attack and yield of bitter gourd (Momordica charantia L). Two sprays at 10-day interval were applied, and data were collected at 3, 5, 7 and 10 days after treatments (DATs), and finally the cumulative means were calculated based on following parameters:  percent fruit infestation and healthy fruits, number of healthy and infested fruits per sq. meter and yield of marketable and infested fruits (ton/ha). All the biopesticides both in individual and combined forms significantly reduced the infestation of the fly at variable levels compared to control. The individual application of Spinosad had provided moderate efficacy. The combination of Spinosad and L. muscarium was the most effective approach to produce the highest percent of healthy fruits (83.32) and the lowest fruit infestation (16.68) protecting most top percent (54.21) of fruits from infestation. The maximum number of marketable fruits per m2 were (13.67), the highest marketable yield (5.15 ton/ha) and the lowest infested yield (0.17 ton/ha) also were obtained from this combined treatment. The fruit yield increased almost twice over control. These suggest that there might be an additive or synergistic action between Spinosad and L. muscarium admixture. However, the Abamectin with L. muscarium treatment did not increase yield, and other parameters significantly suggesting the incompatibility or an antagonistic effect between them. Therefore, based on the findings of the present study, the combination of Spinosad and L. muscarium could be suggested for the management of the cucurbit fruit fly infesting bitter gourd fruits and increasing the yield.J Bangladesh Agril Univ 17(4): 483–489, 2019